Whole‐Device Mass‐Producible Perovskite Photodetector Based on Laser‐Induced Graphene Electrodes. Issue 24 (10th October 2022) - Qu, Menglong; Tian, Yingxin; Cheng, Yi‐Bing; Zhong, Jie; Zhang, Cheng
Abstract: Perovskites have attracted enormous attention in optoelectronics, owing to their excellent optoelectronic properties, low‐cost constituents, and simple solution fabrication approaches. Despite significant advances in large‐scale production of perovskite films, electrode layers—indispensable components of an optoelectronic device—are typically fabricated by depositing noble metals onto perovskite films using complicated techniques, which hinder the large‐scale production of optoelectronic devices. Herein, a whole‐device mass‐producible perovskite photodetector is developed using low‐cost and high‐scalability direct laser writing (DLW) of laser‐induced graphene on a flexible polyimide (PI) film as electrodes, followed by depositing a formamidinium cesium lead triiodide perovskite film using solution methods as the sensing element. The fabricated device exhibits a broad bandwidth (from 365 to 940 nm), a decent responsivity (15.1 mA W −1 ) and detectivity (5.12 × 10 13 Jones), a large photo‐to‐dark current ratio (47.2), and short response time (rise time = 0.4 s and decay time = 0.4 s). The device demonstrates a high humidity (relative humidity = 85%) stability, a long‐term (>48 days) stability, and a high flexibility (0°/90° bending cycles > 1000 times) after encapsulation. The developed whole‐device scalable fabrication sheds light on the mass production and commercialization of perovskite based optoelectronic devices and flexible electronics. Abstract : To promote the commercialization of perovskite‐based optoelectronic devices, large‐scale production of the electrode has received less attention than the perovskite film. Herein, a whole‐device mass‐producible perovskite photodetector is reported using low‐cost and highly scalable laser‐induced graphene as electrodes. Moreover, the fabricated photodetector shows good photodetection performances, high flexibility, and high stability.